Achievement rate and predictive factors of the recommended therapeutical target in patients with axial spondyloarthritis who remain on biological therapy: a prospective cohort study in Spain. Issue 4 (29th April 2022) - Benavent, Diego; Franco-Gómez, Karen; Plasencia-Rodriguez, Chamaida; Novella-Navarro, Marta; Bogas, Patricia; Nieto, Romina; Monjo, Irene; Nuño, Laura; Villalba, Alejandro; Peiteado, Diana; Balsa, Alejandro; Navarro-Compán, Victoria
Abstract : Objectives: To determine the frequency of sustained remission (R) or low diseas activity (LDA) in patients with axial spondyloarthritis (axSpA) undergoing long-term biological therapy and to analyse predictive factors for achieving these outcomes. Design: Prospective, observational cohort study. Setting: Spanish hospital. Participants: Patients with axSpA who initiated biological treatment between 2003 and 2017. Intervention: Assessment of demographic and clinical characteristics at the beginning of treatment and disease activity every 6 months up to a maximum of 2 years. Main outcome measures: Disease activity was measured by Ankylosing Spondylitis Disease Activity Score (ASDAS) and Bath Ankylosing Spondylitis Disease Activity Index and C reactive protein (BASDAI&CRP). Sustained R was defined as ASDAS<1.3 and/or BASDAI <2 and normal CRP while sustained LDA was defined as ASDAS <2.1 and/or BASDAI <4 and normal CRP on at least three consecutive visits. Results: In total 186 patients (66.1% men and 75.3% with radiographic sacroiliitis) were included. Overall, 76.8% of patients achieved ASDAS R/LDA (R53.2%/LDA23.6%) in at least one visit. Forty per cent (R17.6%/LDA22.4%) of the patients fulfilled the sustained ASDAS R/LDA state, whereas only 30.8% maintained this status (R14.8%/LDA15.9%) according to BASDAI&CRP. In the multivariate analysis, male sex (OR=4.01), younger age at the beginning of biological therapy (OR=0.96) and an HLA*B27 positive status (OR=4.30) were associated with achieving sustained ASDAS R/LDA. Conclusions: In clinical practice, around one-third of patients on biological disease-modifying antirheumatic drugs achieve a sustained R/LDA status, but these rates drop to less than one in five when targeting remission, preventing the use of the latter as a feasible target. Male sex, HLA*B27 positivity and younger age at the beginning of biological therapy are the main predictors for achieving sustained R/LDA.